PREFERENCE PATTERNS & DEMAND ANALYSIS OF TRADITIONAL FOOD USING LOGISTIC REGRESSION AND ALMOST IDEAL DEMAND SYSTEM APPROACH - Melda Grahadita; Suharno Suharno; Diah Setyorini Gunawan (Jurnal Pangan dan Agroindustri, 2022)
Garut has many famous traditional foods. These traditional foods continue to exist despite the changing times and changes in people's consumption patterns. Consumers' preferences for traditional foods such as dodol, skin crackers, wajit, rengginang, and processed bananas thoughted to reflect the various patterns of demand for these traditional foods. This study aims to analyze the effect of price, income, education, taste, and promotion as people's preferences for traditional Garut food and analyze people's demand for traditional Garut food, using primary data with a sample of 100 respondents determined based on accidental sampling. The analysis used was logistic regression and the Almost Ideal Demand System (AIDS). This research offers novelty in the form of promotional variables, and demand analysis through the Almost Ideal Demand System (AIDS) approach analyzes the demand for traditional Garut food. The study results are (1) Price has a significant positive effect on people's preferences for traditional food. Income and education do not affect people's preferences for traditional food. Food taste and promotion have a significant positive effect on people's preferences for traditional food. (2) The highest demand for traditional food is dodol. The price changes have not influenced the demand for traditional food or inelastic elasticity. The price elasticity itself is positive inelastic, while most of the cross elasticity is positive, which means that traditional foods replace one another (substitutions).